Dismantling Human Supremacy: Ecopedagogy and Self-Rewilding as Pathways to Embodied Ethics and Cross-Species Solidarity - Shoshana McIntosh; Andrea Natan Feltrin (Relations)
This paper examines the urgent need for a transformative shift in environmental ethics education, specifically challenging the pervasive ideology of human supremacy that shapes contemporary pedagogical approaches. Following ecopedagogy and the critical pedagogy movements, it critiques current educational frameworks that implicitly reinforce human dominance over the more-than-human world. The paper explores the ethical consequences of disembodied, humancentered education, which alienates students from ecological realities and perpetuates environmental degradation and social inequities. In response to these challenges, the paper proposes an alternative ethical framework grounded in cross-species solidarity, relational ethics, and embodied learning. Utilizing approaches such as wild pedagogy and self-rewilding, it emphasizes the importance of immersive, hands-on educational practices that cultivate empathy, multispecies kinship, and ecological consciousness. By fostering these connections, the paper advocates for a reimagined education system that not only dismantles human supremacy but also nurtures more just, regenerative relationships between humans, other-than-human species, and ecosystems. This reorientation in environmental ethics pedagogy offers a critical pathway to confronting the interconnected ecological, social, and cultural crises of our time, while promoting long-term multispecies justice and ecological flourishing.